2006
DOI: 10.1093/ndt/gfl598
|View full text |Cite
|
Sign up to set email alerts
|

Renoprotective effect of COMP-angiopoietin-1 in db/db mice with type 2 diabetes

Abstract: We conclude that COMP-Ang1 delayed the fibrotic changes in the kidney of diabetic db/db mice through its anti-inflammatory or metabolic effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
53
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 20 publications
3
53
0
2
Order By: Relevance
“…In our present H 2 O 2 -induced acute lung injury model, NF-κB levels in nuclear protein extracts were substantially increased, showing that NF-κB is activated and administration of COMP-Ang1 suppressed NF-κB activation induced by H 2 O 2 -inhalation. These findings are consistent with previous reports that Ang1/Tie2 signaling inhibits upregulation of NF-κB activity (Hughes et al, 2003;Lee et al, 2007). Together, we suggest that one likely mechanism of H 2 O 2 -mediated increase in vascular permeability is upregulation of VEGF gene expression by NF-κB activation and that COMP-Ang1-mediated reduction of vascular permeability and VEGF expression is partly due to inhibition of NF-κB activation.…”
Section: Discussionsupporting
confidence: 93%
“…In our present H 2 O 2 -induced acute lung injury model, NF-κB levels in nuclear protein extracts were substantially increased, showing that NF-κB is activated and administration of COMP-Ang1 suppressed NF-κB activation induced by H 2 O 2 -inhalation. These findings are consistent with previous reports that Ang1/Tie2 signaling inhibits upregulation of NF-κB activity (Hughes et al, 2003;Lee et al, 2007). Together, we suggest that one likely mechanism of H 2 O 2 -mediated increase in vascular permeability is upregulation of VEGF gene expression by NF-κB activation and that COMP-Ang1-mediated reduction of vascular permeability and VEGF expression is partly due to inhibition of NF-κB activation.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, the modulating effects of angiopoietins on inflammation, alluded to previously, may also be relevant to glomerulonephritides; however, to explore further the possible roles of angiopoietins in glomerular disease, one will have to manipulate their levels in these same models. In this regard, some promising data were reported by Lee et al,56 who demonstrated that systemic delivery of cartilage oligomeric matrix proteinAng-1 (COMP-Ang-1; a modified form of Ang-1) by adenoviral transduction of hepatocytes reduced renal fibrosis in db/db mice, a model of type 2 diabetes; however, this strategy also caused significant improvement in hyperglycemia, which could itself, at least partly, account for the amelioration of diabetes.…”
Section: Angiopoietin Expression In Acquired Glomerular Diseasementioning
confidence: 99%
“…Most recent studies have demonstrated that the systemic administration of Ang-1 significantly reduced cardiac hypertrophy and myocardial fibrosis in phenylephrine-induced cardiac hypertrophy (45). Furthermore, overexpression of Ang-1 decreased transforming growth factor-1␤ expression and attenuated interstitial fibrosis progression in the kidneys of db/db mice (46). Consistent with these findings, our present study showed that Ang-1 gene therapy resulted in significant decreases in both myocardial fibrosis and in the heart weight-to-body weight ratio (hypertrophy) following myocardial ischemia in db/db mice, implicating the favorable effects of Ang-1 gene therapy on myocardial ischemia-induced adverse remodeling.…”
Section: Ang-1 Rescues Impaired Angiogenesis In Diabetesmentioning
confidence: 99%